Character Education in the Pandemic COVID 19 Era from Elementary School Teachers Point of View - Badawi, Badawi; Nurhayati, Sri; Syarif, Muhammad Ilham; Hidayat, Ahmad Wahyu; Fasa, Muhammad Iqbal (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2024)
The purpose of this study was to understand how to actualize character education in elementary education at the pandemic COVID 19 Era and have teachers' views on it. Participants of the study consisted of six teachers giving character education. The data, collected with semi-structured interviews, were content-analyzed. The results revealed that participants have difficulties in planning, implementing, and evaluating technology-based character education lessons concerning learning outcomes, content, instructional materials, activities, and methods, and they also offered some solutions to them.